Trading Volume: Definitions, Data Analysis, and Implications of Portfolio Theory - Lo, Andrew W.; Wang, Jiang (Review of Financial Studies, 2000)
We examine the implications of portfolio theory for the cross-sectional behavior of equity trading volume. Two-fund separation theorems suggest a natural definition for trading activity: share turnover. If two-fund separation holds, share turnover must be identical for all securities. If (K + 1)-fund separation holds, we show that turnover satisfies an approximately linear K-factor structure. These implications are examined empirically using individual weekly turnover data for NYSE and AMEX securities from 1962 to 1996. We find strong evidence against two-fund separation, and a principal-components decomposition suggests that turnover is well approximated by a two-factor linear model.